Quadriptyque narratif autour de la Seconde Guerre mondiale - Joëlle Ginestet (Lengas)
Four works of fiction about the Second World War published by the Institut d’Etudes Occitanes between 1951 and 1978 fostered the renewal of the narrative form in Occitan fictionalized writings. Shifting from metaphorical terms to historical references and realistic effects, the different points of view of R. Lafont, J. Bodon, P. Pessemesse and P. Bec put language issues and freedom of expression at the centre of our Western society.